CHALLENGES FACED BY ENGLISH TEACHERS IN REMOTE AREA BASED ON SCHOOL-BASED MANAGEMENT POINT OF VIEW (A PHENOMENOLOGICAL STUDY IN JUNIOR HIGH SCHOOLS OF SOUTHEAST WAWONII SUBDISTRICT) - Widyanggara, I Ketut Yudhi; Tanduklangi, Amri; Siam, Siam (Journal of Teaching of English, 2020)
The objective of this research is to find out challenges faced by English teachers in the remote area based on school-based management point of view. The method used in this research was qualitative method with phenomenological approach. It was conducted at SMP Negeri1 Wawonii Tenggara, SMP Negeri 2 Wawonii Tenggara, and SMP Negeri 2 Wawonii Tenggara. The total subjects of this research consisted of 3 English teachers who were not native resident of the study location. The data were collected by in-depth interview, observation, and documentation study. The data were analyzed by using modification of Stevick-Colaizzi-Keen method in Creswell (1998). The data analysis indicated that challenges faced by English teachers based on two aspects of School-based management were as follows: (1) challenges faced by English teachers in remote area based on teachers’ role as a teacher/an educator, (2) challenges faced by English teachers in remote area based on teachers’ role in organizing school-based management. The result showed that there were some challenges that the teachers faced namely: inadequate school facilities, lack of parents’ motivation to their children, lack of students' competence, and overburdened with more duties and responsibilities. To overcome the teachers’ challenges were not only the teachers’ responsibility but also the components of school itself, including headmaster, administrator staff, society and students’ parents to realize their role in School-Based Management and work together with good coordination to get the purpose of implementing School-Based Management.